Fairness-Adjusted Laffer Curve: Strategy versus Direct Method - Hamza Umer (Games, 2018)
This paper reports results from controlled laboratory experiments on the Laffer curve and explores the productivity differences under the strategy method and the direct method. The data collected in Pakistan show no significant productivity difference across the two methods. The paper argues that the Laffer curve is not the result of a simple leisure—income tradeoff; the disutility of work and perceived unfairness of the tax imposed also influence the work decisions. A behavioral model that incorporates these factors induces a “fairness adjusted” Laffer curve with the negative relationship between tax rate and tax revenue showing up after 54% tax rate.